National Peculiarities of the Kalmyk Folk Fairy-tales: Local Plot, Plot Contaminations and Framed Plots - Baira Goryaeva (Oriental Studies, 2018)
The article considers the national peculiarities of the Kalmyk folk fairy-tales represented in the local plot, in plot contaminations and framed plots. Their analysis shows that the Kalmyk folk fairy-tales re| ect the peculiarities of the Mongolian peoples perception of the world and ethnic world-view of Kalmyks formed in certain natural conditions and speci0 c terms of nomadic culture.